If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -4x + 2y)(2y + 3y + 2x) = -1x + xy + 10y Combine like terms: 3x + -4x = -1x (-1x + 2y)(2y + 3y + 2x) = -1x + xy + 10y Reorder the terms: (-1x + 2y)(2x + 2y + 3y) = -1x + xy + 10y Combine like terms: 2y + 3y = 5y (-1x + 2y)(2x + 5y) = -1x + xy + 10y Multiply (-1x + 2y) * (2x + 5y) (-1x * (2x + 5y) + 2y * (2x + 5y)) = -1x + xy + 10y ((2x * -1x + 5y * -1x) + 2y * (2x + 5y)) = -1x + xy + 10y Reorder the terms: ((-5xy + -2x2) + 2y * (2x + 5y)) = -1x + xy + 10y ((-5xy + -2x2) + 2y * (2x + 5y)) = -1x + xy + 10y (-5xy + -2x2 + (2x * 2y + 5y * 2y)) = -1x + xy + 10y (-5xy + -2x2 + (4xy + 10y2)) = -1x + xy + 10y Reorder the terms: (-5xy + 4xy + -2x2 + 10y2) = -1x + xy + 10y Combine like terms: -5xy + 4xy = -1xy (-1xy + -2x2 + 10y2) = -1x + xy + 10y Solving -1xy + -2x2 + 10y2 = -1x + xy + 10y Solving for variable 'x'. Reorder the terms: x + -1xy + -1xy + -2x2 + -10y + 10y2 = -1x + xy + 10y + x + -1xy + -10y Combine like terms: -1xy + -1xy = -2xy x + -2xy + -2x2 + -10y + 10y2 = -1x + xy + 10y + x + -1xy + -10y Reorder the terms: x + -2xy + -2x2 + -10y + 10y2 = -1x + x + xy + -1xy + 10y + -10y Combine like terms: -1x + x = 0 x + -2xy + -2x2 + -10y + 10y2 = 0 + xy + -1xy + 10y + -10y x + -2xy + -2x2 + -10y + 10y2 = xy + -1xy + 10y + -10y Combine like terms: xy + -1xy = 0 x + -2xy + -2x2 + -10y + 10y2 = 0 + 10y + -10y x + -2xy + -2x2 + -10y + 10y2 = 10y + -10y Combine like terms: 10y + -10y = 0 x + -2xy + -2x2 + -10y + 10y2 = 0 The solution to this equation could not be determined.
| -11x-34=43 | | (2x+10)+(3x+50)=90 | | 7.25x+y=443.75 | | y=60x+40 | | (3x-4x+2y)*(2y+3y-2x)=-x+xy+10y | | X+13=6x-32 | | (1/9)x-(1/3)=(-1/6)x-(1/2) | | 1/4a=-1/32 | | -2(3x+6)=-15x | | 3/5x-4(0)=1 | | (3/5)x-2 | | 10=-3/4c | | 4/9x4/9x4/9 | | .875x-2=-.9375x+3 | | 7n+5=8n | | 3/5x-4y=1 | | 10x+5n=100 | | T=-16t^2+0t+29000 | | 95-76=19 | | 3A+6(A+2)= | | 3(6x-1)-4(2x-16)=3(3x+3)-4 | | T=-16t^2+Vt+s | | 3r^2-2r=-5 | | 7x(x+6)=6 | | 3r^2-2r+5=0 | | y^4-y^2+2=0 | | 4x-8x+6=18 | | 15p^2+4p-49=0 | | 7p^2-38-24=0 | | 3x-4(1-x)+18=24 | | k=3y-15+2y | | 171=14x+3 |